COGNITIVE FEATURE STAGES OF TASKS IN INTERNATIONAL COMMUNICATION 3 STUDENT’S BOOK BY AMERICAN CORNER UNTAN: A REVISED BLOOM’S TAXONOMY ANALYSIS - Yosephine Fransiska Nawawi; Sudarsono Sudarsono; Dwi Riyanti (Journal of English Educational Study (JEES), 2023)
This descriptive and qualitative study aims to assess the relevance of the students' materials to the revised Bloom's taxonomy cognitive domain and the prominent cognition aspect in the lesson book. This study focuses on the English student's book "International Communication 3," brought out by American Corner UNTAN. The proof was reviewed using a proof inventory diagram based on the cognitive dimension to categorize the action as either a query or an instructional activity. The outcome revealed that the textbook has 102 activities. The tasks were divided into 80 (78.4%) remembering, 4 (3.9%) understanding, 10 (9.8%) applying, 4 (3.9%) analyzing, 4 (3.9%) evaluating, and 1 (0.98%) creating. The main bulk task was remembering the lowest section of the revised Bloom taxonomy's cognitive pitch. The quantity of low- and high-order thinking skill tasks in every unit is also variable. As a result, it is essential to do more than employ an English lesson book as a teaching tool to upgrade students' critical thinking skills.